READINESS OF EVALUATORS TO ASSESS NON-FORMALLY AND INFORMALLY ACQUIRED COMPETENCES - Teresevičienė, Margarita; Zuzevičiūtė, Vaiva; Kabišaitytė, Sandra (Acta Paedagogica Vilnensia, 2008)
The aim of the paper is to discuss the role and readiness of evaluators to assess non-formally and informally acquired competences of adults entering university. Research made at Vytautas Magnus University prepared university community for new activities – evaluation of competences acquired in labor market, non-formally and informally. The paper presents theoretical background for research based on critical analysis of references. Six main areas of competences of evaluators were defined: preparing evaluation process and planning; preparing candidates for evaluation; preparing process of evaluation; organization and performance of evaluation; development of evaluation process; professional and personal development of evaluators. 35 future evaluators, including university teachers and administration staff members, were trained accordingly to the defined competence areas. Questionnaires were filled in before and after the teaching process. The results showed that evaluators think they can act differently in separate areas of competence evaluation and perform assessment better after teaching sessions. However, it is necessary to organize teaching sessions for evaluators because of complexity of the activities and the new phenomenon at university.